Application of the Pressure-State-Impact-Response model for urban mobility analysis in João Pessoa - Silva, Maria Lucineide Gomes da; Cândido, Gesinaldo Ataíde; Lima, Eduardo Rodrigues Viana de (Sustainability in Debate, 2025)
Urban mobility poses a significant challenge for urban management, particularly in light of the rapid growth dynamics of cities. Inefficient mobility systems in urban centres adversely affect quality of life while generating significant socioeconomic and environmental consequences. This study evaluates the applicability of the GEO Cities model indicators for urban mobility analysis as a municipal decision-making tool. Employing the Pressure-State-Impact-Response (PSIR) framework, we conducted exploratory-descriptive research in João Pessoa, Paraíba’s capital. Our analysis identified 13 thematic indicators relevant to mobility phenomena within the study area. The developed methodology and indicator selection demonstrate transferability to other urban contexts.